Japanese Higher Education as Myth. - McVeigh, Brian J. (Taylor and Francis, 2015)
In this dismantling of the myth of Japanese "quality education", McVeigh investigates the consequences of what happens when statistical and corporatist forces monopolize the purpose of schooling and the boundary between education and employment is blurred.